The evolution of Kenya's animal health surveillance system and its potential for efficient detection of zoonoses - Kahariri, Samuel; Thumbi, S.M.; Bett, Bernard K.; Mureithi, M.W.; Nyaga, N.; Ogendo, A.; Muturi, Mathew; Thomas, Lian F. (Frontiers Media, 2024)
Introduction: Animal health surveillance systems in Kenya have undergone significant changes and faced various challenges throughout the years.